Rat Pial Microvascular Responses to Transient Bilateral Common Carotid Artery Occlusion and Reperfusion: Quercetin’s Mechanism of Action - Lapi, Dominga; Vagnani, Sabrina; Pignataro, Giuseppe; Esposito, Elga; Paterni, Marco; Colantuoni, Antonio (Frontiers in Physiology, 2012)
The aim of the present study was to assess the quercetin’s mechanism of action in rat pial microvessels during transient bilateral common carotid artery occlusion (BCCAO) and reperfusion. Rat pial microcirculation was visualized using fluorescence microscopy through a closed cranial window. Pial arterioles were classified in five orders of branchings. In ischemic rats, 30 min BCCAO and 60 min reperfusion caused arteriolar diameter decrease, microvascular leakage, leukocyte adhesion in venules and reduction of capillary perfusion. Quercetin highest dose determined dilation in all arteriolar orders, by 40 ± 4% of baseline in order 2 vessels, and prevented microvascular permeability [0.15 ± 0.02 Normalized Grey Levels (NGL)], leukocyte adhesion and capillary failure. Inhibition of protein kinase C (PKC) by chelerythrine prior to quercetin attenuated quercetin-induced effects: order 2 arterioles dilated by 19.0 ± 2.4% of baseline, while there was increase in permeability (0.40 ± 0.05 NGL) and leukocyte adhesion with marked decrease in capillary perfusion. Inhibition of tyrosine kinase (TK) by tyrphostin 47 prior to quercetin lessened the responses of the smaller pial arterioles, dilating by 20.7 ± 2.5% of baseline, while leakage increased (0.39 ± 0.04 NGL) accompanied by slight leukocyte adhesion and ameliorated capillary perfusion. Inhibition of eNOS by NG-nitro-L-arginine-methyl ester (L-NAME) prior to PKC or TK reduced the quercetin’s effects on pial arteriolar diameter and leakage. Finally, combined PKC and TK inhibition prior to quercetin abolished quercetin-induced effects. In conclusion, the protective effects of quercetin could be due to different mechanisms resulting in NO release throughout PKC and TK intracellular signaling pathway activation.